KAJI PERFORMANSI REFRIGERAN R-290, R-32, DAN R-410A SEBAGAI ALTERNATIF PENGGANTI R-22 - Rikhard Ufie; Cendy S. Tupamahu; Sefnath J. E. Sarwuna; Jufraet Frans (Fakultas Teknik Universitas Pattimura, 2021)
Refrigerant R-22 is a substance that destroys the ozone layer, so that in the field of air conditioning it has begun to be replaced, among others with refrigerants R-32 and R-410a, and also R-290. Through this research, we want to know how much Coefficient of Performance (COP) and Refrigeration Capacity (Qe) can be produced for the four types of refrigerants. The study was carried out theoretically for the working conditions of the vapor compression cycle with an evaporation temperature (Tevap) of 0, -5, and -10oC, a further heated refrigerant temperature (Î”TSH) of 5 oC, a condensation temperature (Tkond) of 45 oC and a low-cold refrigerant temperature. (Î”TSC) 10 oC and compression power of 1 PK . The results of the study show that the Coefficient of Performance (COP) in the use of R-22 and R-290 is higher than the use of R-32 and R-410a, which are 4,920 respectively; 4,891; 4.690 and 4.409 when working at an evaporation temperature of 0 oC; 4.260; 4,234; 4.060 and 3.812 when working at an evaporation temperature of -5 oC; and amounted to 3,730; 3,685; 3,550 and 3,324 if working at an evaporation temperature of -10 oC. Based on the size of the COP, if this installation works with a compression power of 1 PK, then the cooling capacity of the R-22 and R-290 is higher than the R-32 and R-410a, which are 3,617 respectively. kW; 3,597 kW; 3,449 kW and 3,243 kW. If working at an evaporation temperature of 0 oC; 3.133 kW; 3.114 kW; 2,986 kW and 2,804 kW if working at an evaporation temperature of -5 oC; and 2,741 kW; 2,710 kW; 2,611 kW and 2,445 kW if working at an evaporation temperature of -10oC.